Early inotropes use is associated with higher risk of death and/or severe brain injury in extremely premature infants. (17th August 2020) - Abdul Aziz, Ahmad Nizar; Thomas, Sumesh; Murthy, Prashanth; Rabi, Yacov; Soraisham, Amuchou; Stritzke, Amelie; Kamaluddeen, Majeeda; Al-Awad, Essa; Mohammad, Khorshid
Abstract: Introduction: Extremely premature infants are susceptible to fluctuations in cerebral blood flow due to immaturity of cerebral autoregulation. Inotropes may cause rapid changes to systemic blood pressure and consequently cerebral blood flow, especially within the first 72 hours of life. This period is recognized to carry the greatest risk for cerebral hemorrhage. This study evaluates the incidence of death and/or severe brain injury in extremely preterm infants treated with inotropes in the first 72 hours of life. Methods: Prospective cohort study of infants born ≤29 +0 weeks gestational age (GA) between January 2013 and December 2016. Severe brain injury was defined based on head ultrasound as presence of: grade III or IV intraventricular hemorrhage (IVH), moderate to severe post-hemorrhagic ventricular dilatation (PHVD), or cystic periventricular leukomalacia (cPVL). The association between inotrope use and death and/or brain injury was explored via logistic regression controlling for predefined confounding risk factors. Results: Of 497 eligible infants, 97 (19.5%) received inotropes during the first 72 hours. GA at birth, birth weight (BW), and 5-minute Apgar scores were lower among infants who received early inotropes compared to those not treated with inotropes. A stepwise logistic regression of the predefined confounding factors showed GA, exposure for antenatal steroids, and admission hypothermia to be significant confounding factors. Adjusting for those factors, early use of inotropes was associated with increased risk of death and/or severe brain injury (AOR 4.5; 95%CI: 2.4–8.5), severe brain injury (AOR 4.2; 95% CI: 1.9–8.9), and IVH of any grade (AOR 2.9; 95%CI: 1.7–4.9). Conclusion: Early inotropes use was associated with higher risk of death and/or severe brain injury. Strict indications and strategies for minimizing inotrope use while preventing hypotension should be implemented in the early postnatal care of infants at risk for severe brain injury.